The Complex Intersection of Race and Rurality: The Detrimental Effects of Race-Neutral Rural Health Policies (Mary Ann Liebert, 2022)
In this commentary, we discuss our experiences as women of different races growing up in the same rural area and how these experiences relate to health and health policy. Despite nearly five million Black people living in nonmetro areas, rural Black Americans face erasure in the rural narrative and the policies enacted to support them. This is detrimental to the overall uplifting of rural communities and to the elimination of the compounded disparities of being rural and Black. We aim to bring to life rural America for Black and White residents and the impact of the policies that shape it.